1985
DOI: 10.1037/0022-006x.53.3.406
|View full text |Cite
|
Sign up to set email alerts
|

Catecholamine secretion as a function of perceived coping self-efficacy.

Abstract: The present research tested the hypothesis that perceived coping self-efficacy mediates the effects of environmental events on catecholamine secretion. Differential levels of perceived self-efficacy were induced in phobic subjects through modeling. Their level of catecholamine secretion was then measured as they were presented coping tasks in their high, medium, and low ranges of perceived self-efficacy. High perceived self-efficacy was accompanied by low levels of plasma epinephrine and norepinephrine during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
102
0
6

Year Published

1990
1990
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 234 publications
(121 citation statements)
references
References 22 publications
12
102
0
6
Order By: Relevance
“…The results are consistent with the other studies presenting the relationship of SelfEfficacy with stress (BANDURA et al 1985). The results of this study support the proposition that self-efficacy has psychological benefits.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The results are consistent with the other studies presenting the relationship of SelfEfficacy with stress (BANDURA et al 1985). The results of this study support the proposition that self-efficacy has psychological benefits.…”
Section: Discussionsupporting
confidence: 83%
“…Meanwhile, low self-efficacy indicates low levels of self-confidence, negative self-evaluation, and the inability to produce a planned outcome when tasks are given (APPELBAUM & HARE 1996). High SE has been related to a wide range of physiological measures including lower catecholamine responsivity during stress (BANDURA et al 1985), pre-competitive anxiety and subjective performance among athletes (NICHOLLS 2010), and better psychological adjustment to highly stressful life changes and events, such as aging (KRAAIJ 2002, BENKA et al 2014.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, several researchers have examined the important question of whether or not self-efficacy actually plays a causal role in influencing human functioning or is simply a reflection of past performance. Evidence converges to indicate that self-efficacy does play a causal role in determining a diverse array of outcomes [20,25,26].…”
Section: Introductionmentioning
confidence: 99%
“…Someone with low coping self-efficacy in addition believes that he or she is incapable of clearing their minds of invasive thoughts (Bandura 1997;Lazarus and Folkman 1984a, b). People with high coping self-efficacy, on the other hand, believe that they can avoid cognitive overload, have control over intrusive thoughts, and proactively shape situations to make them less threatening (Bandura et al 1985). For instance, reported that for Hurricane Opal survivors, perceived coping self-efficacy had a significant mediating effect in explaining who did not have lasting distress from the trauma .…”
Section: Coping Orientations and Project Failurementioning
confidence: 99%